Sino-Russian rapprochement and Greater Eurasia: From geopolitical pole to international society?. Issue 1 (January 2021) - Lukin, Alexander; Novikov, Dmitry
Can international anarchy be stabilized, if not globally, then at least regionally? Those scholars who give a positive answer usually refer to the North Atlantic community which can be categorized as an international society from the viewpoint of the English school. The emergence of such a community outside the West is traditionally considered hardly possible. However, this article argues that it may already be emerging in Eurasia, with Russia and China being the key drivers of this trend. In the past few years, these two powers have put forward a number of major initiatives aimed at developing transport networks and logistics, and deepening economic and institutional ties between different parts of the continent. These include but are not limited to Eurasian Economic Union, supported by Russia, and China's Belt and Road Initiative. Together, Moscow and Beijing began to form a new platform for security and economic cooperation "from Kaliningrad to Shanghai"—the community of Greater Eurasia. Based on the analysis of the geopolitical logic of these initiatives, this article suggests that a new, non-Western international society may be forming in Eurasia among the states with different political systems and cultures, but common geopolitical aims and fears.